Antimicrobial, Antiviral and Immunomodulatory Activity Studies of Pelargonium sidoides (EPs® 7630) in the Context of Health Promotion - Herbert Kolodziej (MDPI AG, 2011)
Pelargonium species contribute significantly to the health care of a large population in the Southern African region, as part of a long-standing medical system intimately linked to traditional healing practices. Most notably, extracts of the roots of P. sidoides have commonly been applied for the treatment of dysentery and diarrhoea but only occasionally for respiratory complaints. Clinical trials have shown that a modern aqueous-ethanolic formulation of P. sidoides extracts (EPs® 7630) is an efficacious treatment for disorders of the respiratory tract, for example bronchitis and sinusitis. It should be noted that EPs® 7630 is the most widely investigated extract and therefore is the focus of this review. In order to provide a rationale for its therapeutic activity extracts have been evaluated for antibacterial activity and for their effects on non-specific immune functions. Only moderate direct antibacterial capabilities against a spectrum of bacteria, including Mycobacteria strains, have been noted. In contrast, a large body of in vitro studies has provided convincing evidence for an anti-infective principle associated with activation of the non-specific immune system. Interestingly, significant inhibition of interaction between bacteria and host cells, a key to the pathogenesis of respiratory tract infections, has emerged from recent studies. In addition, antiviral effects have been demonstrated, including inhibition of the replication of respiratory viruses and the enzymes haemagglutinin and neuraminidase. Besides, an increase of cilliary beat frequency of respiratory cells may contribute to the beneficial effects of P. sidoides extracts. This example provides a compelling argument for continuing the exploration of Nature and traditional medical systems as a source of therapeutically useful herbal medicines.